Proceedings of the 5th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2013
DOI: 10.1145/2516540.2516564
|View full text |Cite
|
Sign up to set email alerts
|

Using speech, GUIs and buttons in police vehicles

Abstract: The Project54 mobile system for law enforcement developed at the University of New Hampshire integrates the control of disparate law enforcement devices such as radar, VHF radio, video, and emergency lights and siren. In addition it provides access to state and national law enforcement databases via wireless data queries. Officers using Project54 are free to intermix three different user interface modes: the device native controls; an LCD touchscreen with keyboard and mouse; and voice commands with voice feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Estimating the user's workload is helpful for many situations where people interact with computing devices or machines. One example is the automotive domain where it is important not to overload the driver as they interact with in-vehicle devices [28] or communicate with remote conversants [21,38], since performance degrades with increasing workload [6]. With automated driving modes and non-driving-related activities [37], workload estimation can be useful to track and support the driver's reengagement in the driving task [20].…”
Section: Contribution Statementmentioning
confidence: 99%
“…Estimating the user's workload is helpful for many situations where people interact with computing devices or machines. One example is the automotive domain where it is important not to overload the driver as they interact with in-vehicle devices [28] or communicate with remote conversants [21,38], since performance degrades with increasing workload [6]. With automated driving modes and non-driving-related activities [37], workload estimation can be useful to track and support the driver's reengagement in the driving task [20].…”
Section: Contribution Statementmentioning
confidence: 99%
“…Prior studies have found officers' use of in-vehicle technologies while driving (Yager et al, 2015), fatigue (Vila & Kenney, 2002), and lack of sufficient training in handling high-demand situations (e.g., pursuit situations, multi-tasking) (Hembroff et al, 2018) are major contributors of motor vehicle crashes for LEOs. In addition, LEOs are continuously surrounded by the high noise level inside the police vehicles which can lead to poor speech recognition, and complexity of tasks which can interrupt their concentration on tasks and ultimately increase their CW (Miller & Kun, 2013;Shahini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%